Transcendental Humanism for Equality: Abdurrahman Wahid’s Thoughts on Women - Iswahyudi (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The study of feminism is currently dominated by women, even though gender-fair relations will not be realized without awareness from the male side. One of the Indonesian male intellectuals who has a high response to women is Abdurrahman Wahid. Unfortunately, the study of Abdurrahman Wahid still revolves around three studies, namely, as a great thinker in Pluralism, liberalism, and pribumisasi, or privatization of Islam; as a political actor and as an educational thinker. Therefore, the purpose of this paper is first to find the pattern of Abdurrahman Wahid’s thinking about women, second, to look for influencing factors; and third, to look for the relevance of his thoughts. This study is a literature study, which is a study that relies on the main source of Abdurrahman Wahid's works or writings on women. The works or comments of intellectuals who discuss Abdurrahman Wahid's thoughts on women are complementary sources of this paper. Various thoughts of Abdurrahman Wahid will be researched and reduced based on the themes discussed about women. These themes are then analyzed using qualitative content analysis. The study found three things. First, Abdurrahman Wahid’s style of thinking about women is transcendental humanism. This pattern is a discontinuity from the previous thought, where the perspectives of Mu’tazilah, Marxian, and Sufism also give color to his thoughts. Second, the factors that affect the pattern are family, education, life experience, and madhhab thought. These factors are the structure of cultural and ideological understanding. Third, the religious and patriarchal Indonesian people make Abdurrahman Wahid’s thoughts relevant. Abdurrahman Wahid’s modality and habitus (pattern of thinking) allow his thinking to be received and developed by the community. However, this paper has not outlined the continuity and change of Abdurrahman Wahid’s thinking and does not see her intellectual position compared to other female thinkers.